A method for effectively detecting the anionicity of polyacrylamide

By converting the polyacrylamide dry powder into a working electrode and assembled into a three-electrode system, the current response curve is detected and the anion degree is calculated, the problem of poor detection accuracy in the prior art is solved, and the accuracy and efficient detection of the anion degree of polyacrylamide is achieved.

CN119125256BActive Publication Date: 2025-04-29GUANGDONG SHOUXIN POLYMER SYNTHESIS SCIENCE CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411267959.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-04-29
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

In the prior art, the accuracy of detecting the anion of polyacrylamide is poor, which affects product quality and application effect.

Method used

By converting the polyacrylamide dry powder into a working electrode, assembled into a three-electrode system, it is placed in the electrolyte solution to detect the current response curve, calculate the charged group content and calculate the anion degree.

Benefits of technology

It realizes accurate detection of the anionicity of polyacrylamide, which is suitable for the detection of low and high anionicity, with short test cycles, simple operation, and high testing efficiency and applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119125256B_ABST
    Figure CN119125256B_ABST
Patent Text Reader

Abstract

The present invention provides a method capable of effectively detecting the anionicity of polyacrylamide. Dry polyacrylamide powder is assembled into electrodes, the content of charged groups in the dry polyacrylamide powder is obtained according to electrochemical testing, and the anionicity of polyacrylamide is calculated according to the content of charged groups. The method can accurately test the anionicity of polyacrylamide. At the same time, the detection method has a short test cycle and high test efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyacrylamide detection, and in particular to a method capable of effectively detecting the anion degree of polyacrylamide. Background Art

[0002] Polyacrylamide is an important water-soluble polymer, widely used in oil extraction, water treatment, papermaking, textile and other fields.

[0003] In the classification of polyacrylamide, anionic polyacrylamide is an important type. Anionic polyacrylamide has good water solubility and can quickly form a uniform solution in water. At the same time, anionic polyacrylamide often has a higher molecular weight, which makes it have excellent performance in flocculation, thickening and other aspects. For example, anionic polyacrylamide has a good flocculation effect on suspended particles in water, which can make these suspended particles quickly aggregate and precipitate. This feature can make it better used as a flocculant in the treatment of tailings. For another example, anionic polyacrylamide can effectively increase the viscosity of the solution at low concentrations, which enables it to be better used in coatings, glues and other fields.

[0004] For anionic polyacrylamide, anionicity is one of the important indicators to measure its performance. Accurate detection of anionicity of polyacrylamide is of great significance to ensure its product quality and application effect. However, the accuracy of current detection methods such as turbidimetry and precipitation method is poor. Summary of the invention

[0005] Based on the above problems, the present invention provides a method for effectively detecting the anionicity of polyacrylamide. The anionicity of polyacrylamide can be accurately detected by the detection method.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] A method for effectively detecting the anionicity of polyacrylamide comprises the following steps:

[0008] S1: Transfer the polyacrylamide powder to the current collector and press it into a working electrode;

[0009] S2: Assembling the working electrode, the counter electrode and the reference electrode into a three-electrode system;

[0010] S3: placing the three-electrode system in an electrolyte solution, and detecting a current response curve of the three-electrode system at different potentials;

[0011] S4: calculating the content of charged groups in the polyacrylamide dry powder according to the current response curve;

[0012] S5: Calculating the anionicity of the polyacrylamide powder according to the content of the charged groups and the molar number of the polyacrylamide powder.

[0013] In some embodiments, the calculation formula of the anionicity is: the anionicity = the number of moles of the charged groups / the number of moles of the polyacrylamide×100%.

[0014] In some embodiments, the current response curve of the three-electrode system at different potentials is detected by cyclic voltammetry or constant potential method.

[0015] In some embodiments, calculating the content of charged groups in the polyacrylamide dry powder according to the current response curve includes the following steps: integrating the current response curve to calculate the quantity of electricity at different potentials; and calculating the content of charged groups in the polyacrylamide dry powder according to the quantity of electricity.

[0016] In some of the embodiments, during the detection of the current response of the three-electrode system at different potentials, the potential range is -0.5V-1V and the scanning speed is 5mV / s-50mV / s.

[0017] In some embodiments, the particle size of the polyacrylamide dry powder is 20 μm-75 μm.

[0018] In some of the embodiments, the concentration of the electrolyte in the electrolyte solution is 0.1 mol / L-0.5 mol / L.

[0019] In some embodiments, the electrolyte in the electrolyte solution includes one or more of sodium chloride, sodium sulfate and potassium chloride.

[0020] In some embodiments, the thickness of the current collector is 0.1 mm-0.5 mm.

[0021] In some embodiments, the material of the current collector includes one or more of platinum, gold and silver.

[0022] In some embodiments, the pressing pressure is 5 MPa-10 MPa.

[0023] In some embodiments, the pressing time is 8 min-15 min.

[0024] In some embodiments, the material of the counter electrode includes platinum, and the reference electrode is a saturated calomel electrode.

[0025] Beneficial Effects

[0026] The present invention prepares polyacrylamide dry powder into a working electrode, and assembles the working electrode, the counter electrode and the reference electrode into a three-electrode system. Then, the three-electrode system is placed in an electrolyte solution, and the current response curve of the three-electrode system at different potentials is detected. Then, the content of the charged group in the polyacrylamide dry powder is calculated according to the current response curve. Then, the anionicity of the polyacrylamide is calculated according to the content of the charged group and the molar number of the polyacrylamide dry powder. In the method for detecting the anionicity of polyacrylamide, the charging condition of the polyacrylamide can be accurately reflected by the current response curve, and the anionicity of the polyacrylamide can be accurately tested.

[0027] Furthermore, the detection method has wide applicability to the detection of anionicity of polyacrylamide, and can obtain relatively accurate anionicity test results for both polyacrylamide with low anionicity and polyacrylamide with high anionicity.

[0028] Furthermore, the detection method has a short test cycle and high test efficiency. From the preparation of the polyacrylamide working electrode to the calculation of the anion degree, the entire test process can be completed within a few hours, which can meet the rapid detection needs in actual production.

[0029] Furthermore, the detection method is relatively simple to operate and does not require complex testing equipment and cumbersome operating steps. During the test, an electrochemical workstation is mainly used to detect the anionicity of polyacrylamide, which has been promoted and used. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flowchart of a method for effectively detecting the anionicity of polyacrylamide according to one embodiment of the present invention. DETAILED DESCRIPTION

[0031] In the classification of polyacrylamide, anionic polyacrylamide is an important type. Anionic polyacrylamide has good water solubility and can quickly form a uniform solution in water. At the same time, anionic polyacrylamide often has a higher molecular weight, which makes it have excellent performance in flocculation, thickening and other aspects. Anionicity is one of the important indicators to measure the performance of polyacrylamide. Accurate determination of the anionicity of polyacrylamide is of great significance to ensure its product quality and application effect. However, the accuracy of current detection methods such as turbidimetry and precipitation method is poor.

[0032] See also Figure 1One embodiment of the present invention provides a method for effectively detecting the anionicity of polyacrylamide, comprising the following steps: S1: transferring polyacrylamide dry powder to a current collector and pressing it into a working electrode; S2: assembling the working electrode, a counter electrode and a reference electrode into a three-electrode system; S3: placing the three-electrode system in an electrolyte solution, and detecting the current response curve of the three-electrode system at different potentials; S4: calculating the content of charged groups in the polyacrylamide dry powder according to the current response curve; S5: calculating the anionicity of the polyacrylamide dry powder according to the content of the charged groups and the molar number of the polyacrylamide dry powder.

[0033] In this embodiment, polyacrylamide dry powder is made into a working electrode, and the working electrode, the counter electrode and the reference electrode are assembled into a three-electrode system. Then the three-electrode system is placed in an electrolyte solution, and the current response curve of the three-electrode system at different potentials is detected. The content of the charged group in the polyacrylamide dry powder is calculated based on the current response curve. Then, the anionicity of the polyacrylamide is calculated based on the content of the charged group and the molar number of the polyacrylamide dry powder. In the method for detecting the anionicity of polyacrylamide, the charging condition of the polyacrylamide can be accurately reflected by the current response curve, and the anionicity of the polyacrylamide can be accurately tested.

[0034] Furthermore, the detection method has a short test cycle and high test efficiency. From the preparation of the polyacrylamide working electrode to the calculation of the anion degree, the entire test process can be completed within a few hours, which can meet the rapid detection needs in actual production.

[0035] Furthermore, the detection method is relatively simple to operate and does not require complex testing equipment and cumbersome operating steps. During the test, an electrochemical workstation is mainly used to detect the anionicity of polyacrylamide, which has been promoted and used.

[0036] Furthermore, the detection method has wide applicability to the detection of anionicity of polyacrylamide, and can obtain relatively accurate anionicity test results for both low anionicity polyacrylamide and high anionicity polyacrylamide.

[0037] It is understood that the polyacrylamide powder can be obtained by drying the polyacrylamide sample to a constant weight at a certain temperature to remove the influence of moisture on the test results. Optionally, the drying temperature is 80°C-100°C and the drying time is 1h-3h. Further optionally, the drying can be carried out in a vacuum drying oven.

[0038] Optionally, the drying temperature can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc. It is understandable that the drying temperature can also be other suitable selections within the range of 80°C-100°C.

[0039] Optionally, the drying time can be 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h, etc. Of course, the drying time is not limited to the values ​​listed above, and the drying time can also be other suitable selections within the range of 1h-3h.

[0040] In some embodiments, the calculation formula of the anionicity is: the anionicity = the molar number of the charged group / the molar number of the polyacrylamide × 100%. The anionicity of polyacrylamide can be accurately tested by this formula, and at the same time, the formula is relatively simple and can quickly calculate the anionicity of polyacrylamide.

[0041] In some embodiments, the current response curve of the three-electrode system at different potentials is detected by cyclic voltammetry or constant potential method. Cyclic voltammetry or constant potential method has good stability, which can improve the stability of the current response curve test. When multiple current response curves need to be tested, the multiple current response curves can have good consistency, thereby further improving the accuracy of the polyacrylamide anionicity test.

[0042] In some embodiments, calculating the content of charged groups in the polyacrylamide dry powder according to the current response includes the following steps: integrating the current response curve to calculate the quantity of electricity at different potentials; and calculating the content of charged groups in the polyacrylamide dry powder according to the quantity of electricity.

[0043] In some of the embodiments, in the current response process of the three-electrode system at different potentials, the potential range is -0.5V-1V, and the scanning speed is 5mV / s-50mV / s. Within the potential range and the scanning speed range, a current response curve that can better reflect the actual situation of polyacrylamide can be obtained, which is conducive to further improving the detection accuracy of the anionic degree of polyacrylamide. Optionally, the potential range is -0.5V-0.5V. It is understandable that the potential range can also select a suitable potential range within the range of -0.5V-1V. Optionally, the scanning speed can be 5mV / s, 10mV / s, 15mV / s, 20mV / s, 25mV / s, 30mV / s, 35mV / s, 40mV / s, 45mV / s, 50mV / s, etc. It is understandable that the scanning speed can also make other suitable choices within the range of 5mV / s-50mV / s.

[0044] In some embodiments, the particle size of the polyacrylamide dry powder is 20μm-75μm. If the particle size of the polyacrylamide dry powder is too small, the gap between the polyacrylamide dry powder particles may be too small, affecting the transmission of the conductive particles in the working electrode. If the particle size of polyacrylamide is too large, it is difficult to compact, and the particles are easily broken and collapsed, causing the working electrode to collapse. The particle size of the polyacrylamide dry powder can obtain a higher compaction density within this range, and the obtained working electrode is not easy to collapse. That is, by selecting the particle size of the polyacrylamide dry powder, the working electrode can take into account both a higher compaction density and a more stable structure. Optionally, the particle size of the polyacrylamide dry powder can be 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, etc. Of course, it is understandable that the particle size of the polyacrylamide dry powder can also be selected in other suitable ranges within 20μm-75μm.

[0045] In some embodiments, the thickness of the current collector is 0.1mm-0.5mm. When the thickness of the current collector is too small, the strength of the current collector is low, and it is difficult to form a working electrode with a stable structure. When the thickness of the current collector is too large, the weight of the working electrode will increase, which is not conducive to the assembly of the three-electrode system in the later stage. Optionally, the thickness of the current collector can be but is not limited to 0.1mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, etc. It is understandable that the thickness of the current collector can also be other suitable choices within the range of 0.1mm-0.5mm.

[0046] In some embodiments, the material of the current collector includes one or more of platinum, gold and silver. These materials have good electrical conductivity, which is conducive to improving the transmission of current in the three-electrode system and further improving the accuracy of polyacrylamide anion degree detection.

[0047] In some embodiments, the pressing pressure is 5MPa-10MPa. If the pressing pressure is too small, it is difficult to obtain a structurally stable working electrode. If the pressing pressure is too large, the current collector may be damaged, and it is not conducive to obtaining a structurally stable working electrode. Optionally, the pressing pressure can be 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa, etc. It is understandable that the pressing pressure can also be selected in other suitable ranges within the range of 5MPa-10MPa.

[0048] In some embodiments, the pressing time is 8min-15min. If the pressing time is too short, it is difficult to obtain a working electrode with a stable structure. If the pressing time is too long, the current collector may be damaged, which is not conducive to obtaining a working electrode with a stable structure. At the same time, the time for detecting the anion degree of polyacrylamide will be prolonged, and the detection efficiency will be reduced. Optionally, the pressing time can be 8min, 9min, 10min, 11min, 12min, 13min, 14min, 15min, etc. It is understandable that the pressing time can also be selected in other suitable ways within the range of 8min-15min.

[0049] In some embodiments, the concentration of the electrolyte in the electrolyte solution is 0.1mol / L-0.5mol / L. Too small a concentration of the electrolyte in the electrolyte solution is not conducive to the transmission of the conductive particles in the three-electrode system, and too large a concentration of the electrolyte in the electrolyte solution may increase the internal resistance of the three-electrode system. Therefore, the concentration of the electrolyte in the electrolyte solution within this range can enable the conductive particles to have a higher transmission speed in the three-electrode system, and improve the timeliness of the current response of the three-electrode system at different potentials. Optionally, the concentration of the electrolyte in the electrolyte solution can be 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, etc. It is understandable that the concentration of the electrolyte in the electrolyte solution can also be other suitable choices within the range of 0.1mol / L-0.5mol / L. Optionally, the electrolyte in the electrolyte solution includes one or more of sodium chloride, sodium sulfate and potassium chloride. Optionally, the three-electrode system is placed in the electrolyte solution by immersing the three-electrode system in the electrolyte solution.

[0050] In some embodiments, the material of the counter electrode includes platinum, and the reference electrode is a saturated calomel electrode.

[0051] Another embodiment of the present invention provides a method for effectively detecting the anionicity of polyacrylamide, comprising the following steps:

[0052] S10: Dry the polyacrylamide sample at 80° C.-100° C. for 1 h-3 h until constant weight is obtained to obtain polyacrylamide dry powder.

[0053] S20: Transferring the polyacrylamide powder to the current collector and pressing it into a working electrode. The particle size of the polyacrylamide powder is 20 μm-75 μm. The material of the current collector includes one or more of platinum, gold and silver. The thickness of the current collector is 0.1 mm-0.5 mm. The pressing pressure is 5 MPa-10 MPa. The pressing time is 8 min-15 min.

[0054] S30: Assemble a working electrode, a counter electrode and a reference electrode into a three-electrode system. The counter electrode is made of platinum, and the reference electrode is a saturated calomel electrode.

[0055] S40: placing the three-electrode system in an electrolyte solution, and detecting the current response curve of the three-electrode system at different potentials by cyclic voltammetry or constant potential method. The electrolyte in the electrolyte solution includes one or more of sodium chloride, sodium sulfate and potassium chloride. The concentration of the electrolyte in the electrolyte solution is 0.1mol / L-0.5mol / L. In the process of detecting the current response curve of the three-electrode system at different potentials, the potential range is -0.5V-1V, and the scanning speed is 5mV / s-50mV / s.

[0056] S50: Integrate the current response curve and calculate the charge at different potentials; calculate the content of charged groups in the polyacrylamide dry powder based on the charge.

[0057] S60: Calculate the anionicity of the polyacrylamide powder according to the content of the charged groups and the molar number of the polyacrylamide powder. The calculation formula of the anionicity is: anionicity = molar number of charged groups / molar number of polyacrylamide × 100%.

[0058] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.

[0059] Example 1

[0060] The polyacrylamide sample in this embodiment is a polyacrylamide sample with known anionicity, wherein the anionicity of the polyacrylamide sample is 10.5%.

[0061] The method for detecting the anionicity of polyacrylamide in this embodiment is:

[0062] S101: Dry the polyacrylamide sample at 80° C. for 2 h to obtain polyacrylamide dry powder.

[0063] S102: Coat a polyacrylamide powder with a particle size of 70 μm onto a platinum current collector with a thickness of 0.2 mm, and press it into a working electrode at a pressure of 6 MPa for 10 min.

[0064] S103: Assemble a working electrode, a counter electrode and a reference electrode into a three-electrode system. The counter electrode is a platinum electrode, and the reference electrode is a saturated calomel electrode.

[0065] S104: The three-electrode system is immersed in a sodium chloride solution with a concentration of 0.2 mol / L, and a current response curve of the three-electrode system at a potential of -0.5 V to 0.5 V is detected by cyclic voltammetry with a scanning speed of 20 mV / s.

[0066] S105: Integrate the current response curve to calculate the electric quantity at different potentials; calculate the content of charged groups in the polyacrylamide dry powder based on the electric quantity.

[0067] S106: Calculate the anionicity of the polyacrylamide powder according to the content of the charged groups and the molar number of the polyacrylamide powder. The calculation formula of the anionicity is: anionicity = molar number of charged groups / molar number of polyacrylamide × 100% = 10.8%.

[0068] The relative error between the anionicity detected by the detection method in this embodiment and the known anionicity is δ1=(10.8%-10.5%) / 10.5%×100%=2.9%.

[0069] Comparative Example 1

[0070] This comparative example uses the same polyacrylamide sample as in Example 1.

[0071] This comparative example uses turbidimetry to detect the anionicity of the polyacrylamide sample. The detection method is: dry the polyacrylamide sample at 80°C for 2 hours to obtain polyacrylamide dry powder. Weigh the polyacrylamide dry powder with a particle size of 70 μm and dissolve it in water, add barium chloride solution, measure the turbidity of the solution with a spectrophotometer, and calculate the anionicity of the polyacrylamide sample based on the turbidity. The test result is 11.4%.

[0072] The relative error between the anionicity obtained by the detection method in this comparative example and the known anionicity is δ2=(11.4%-10.5%) / 10.5%×100%=8.6%.

[0073] Comparative Example 2

[0074] This comparative example uses the same polyacrylamide sample as in Example 1.

[0075] This comparative example uses a precipitation method to detect the anionicity of the polyacrylamide sample. The detection method is: dry the polyacrylamide sample at 80°C for 2 hours to obtain a polyacrylamide powder. Weigh the polyacrylamide powder with a particle size of 70 μm and dissolve it in water, add hexadecyltrimethylammonium bromide, centrifuge the reaction solution after the reaction is completed, collect the precipitate, then wash the precipitate with ethanol, and finally dry the precipitate to constant weight. Calculate the anionicity of the polyacrylamide sample based on the mass of the precipitate. The test result is 11.7%.

[0076] The relative error between the anionicity obtained by the detection method in this comparative example and the known anionicity is δ3=(11.7%-10.5%) / 10.5%×100%=11.4%.

[0077] Example 2

[0078] The polyacrylamide sample in this embodiment is a polyacrylamide sample with known anionicity, wherein the anionicity of the polyacrylamide sample is 21.7%.

[0079] The method for detecting the anionicity of polyacrylamide in this embodiment is:

[0080] S101: Dry the polyacrylamide sample at 80° C. for 2 h to obtain polyacrylamide dry powder.

[0081] S102: Coat a polyacrylamide powder with a particle size of 70 μm onto a platinum current collector with a thickness of 0.2 mm, and press it into a working electrode at a pressure of 6 MPa for 10 min.

[0082] S103: Assemble a working electrode, a counter electrode and a reference electrode into a three-electrode system. The counter electrode is a platinum electrode, and the reference electrode is a saturated calomel electrode.

[0083] S104: The three-electrode system is immersed in a sodium chloride solution with a concentration of 0.3 mol / L, and a current response curve of the three-electrode system at a potential of -0.5 V to 0.5 V is detected by cyclic voltammetry with a scanning speed of 30 mV / s.

[0084] S105: Integrate the current response curve to calculate the electric quantity at different potentials; calculate the content of charged groups in the polyacrylamide dry powder based on the electric quantity.

[0085] S106: Calculate the anionicity of the polyacrylamide powder according to the content of the charged groups and the molar number of the polyacrylamide powder. The calculation formula of the anionicity is: anionicity = molar number of charged groups / molar number of polyacrylamide × 100% = 21.5%.

[0086] The relative error between the anionicity detected by the detection method in this embodiment and the known anionicity is δ4=︱21.5%-21.7%︱ / 21.7%×100%=0.9%.

[0087] Comparative Example 3

[0088] This comparative example uses the same polyacrylamide sample as in Example 2.

[0089] This comparative example uses turbidimetry to detect the anionicity of the polyacrylamide sample. The detection method is: dry the polyacrylamide sample at 80°C for 2 hours to obtain polyacrylamide dry powder. Weigh the polyacrylamide dry powder with a particle size of 70 μm and dissolve it in water, add barium chloride solution, measure the turbidity of the solution with a spectrophotometer, and calculate the anionicity of the polyacrylamide sample based on the turbidity. The test result is 22.4%.

[0090] The relative error δ5 between the anionicity obtained by the detection method in this comparative example and the known anionicity is = (22.4% - 21.7%) / 21.7% × 100% = 3.2%.

[0091] Comparative Example 4

[0092] This comparative example uses the same polyacrylamide sample as in Example 2.

[0093] This comparative example uses a precipitation method to detect the anionicity of the polyacrylamide sample. The detection method is: dry the polyacrylamide sample at 80°C for 2 hours to obtain a polyacrylamide powder. Weigh the polyacrylamide powder with a particle size of 70 μm and dissolve it in water, add hexadecyltrimethylammonium bromide, centrifuge the reaction solution after the reaction is completed, collect the precipitate, then wash the precipitate with ethanol, and finally dry the precipitate to constant weight. Calculate the anionicity of the polyacrylamide sample based on the mass of the precipitate. The test result is 22.7%.

[0094] The relative error between the anionicity obtained by the detection method in this comparative example and the known anionicity is δ6=(22.7%-21.7%) / 21.7%×100%=4.6%.

[0095] Example 3

[0096] The polyacrylamide sample in this embodiment is a polyacrylamide sample with known anionicity, wherein the anionicity of the polyacrylamide sample is 31.2%.

[0097] The method for detecting the anionicity of polyacrylamide in this embodiment is:

[0098] S101: Dry the polyacrylamide sample at 80° C. for 2 h to obtain polyacrylamide dry powder.

[0099] S102: Coat a polyacrylamide powder with a particle size of 70 μm onto a platinum current collector with a thickness of 0.2 mm, and press it into a working electrode at a pressure of 6 MPa for 10 min.

[0100] S103: Assemble a working electrode, a counter electrode and a reference electrode into a three-electrode system. The counter electrode is a platinum electrode, and the reference electrode is a saturated calomel electrode.

[0101] S104: The three-electrode system is immersed in a sodium chloride solution with a concentration of 0.3 mol / L, and a current response curve of the three-electrode system at a potential of -0.5 V to 0.5 V is detected by cyclic voltammetry at a scanning rate of 40 mV / s.

[0102] S105: Integrate the current response curve to calculate the electric quantity at different potentials; calculate the content of charged groups in the polyacrylamide dry powder based on the electric quantity.

[0103] S106: Calculate the anionicity of the polyacrylamide powder according to the content of the charged groups and the molar number of the polyacrylamide powder. The calculation formula of the anionicity is: anionicity = molar number of charged groups / molar number of polyacrylamide × 100% = 31.6%.

[0104] The relative error between the anionicity detected by the detection method in this embodiment and the known anionicity is δ7=(31.6%-31.2%) / 31.2%×100%=1.3%.

[0105] Comparative Example 5

[0106] This comparative example uses the same polyacrylamide sample as in Example 3.

[0107] This comparative example uses turbidimetry to detect the anionicity of the polyacrylamide sample. The detection method is: dry the polyacrylamide sample at 80°C for 2 hours to obtain polyacrylamide dry powder. Weigh the polyacrylamide dry powder with a particle size of 70 μm and dissolve it in water, add barium chloride solution, measure the turbidity of the solution with a spectrophotometer, and calculate the anionicity of the polyacrylamide sample based on the turbidity. The test result is 33.3%.

[0108] The relative error between the anionicity obtained by the detection method in this comparative example and the known anionicity is δ8=(33.3%-31.2%) / 31.2%×100%=6.7%.

[0109] Comparative Example 6

[0110] This comparative example uses the same polyacrylamide sample as in Example 3.

[0111] This comparative example uses a precipitation method to detect the anionicity of the polyacrylamide sample. The detection method is: dry the polyacrylamide sample at 80°C for 2 hours to obtain a polyacrylamide powder. Weigh the polyacrylamide powder with a particle size of 70 μm and dissolve it in water, add hexadecyltrimethylammonium bromide, centrifuge the reaction solution after the reaction is completed, collect the precipitate, then wash the precipitate with ethanol, and finally dry the precipitate to constant weight. Calculate the anionicity of the polyacrylamide sample based on the mass of the precipitate. The test result is 28.4%.

[0112] The relative error between the anionicity obtained by the detection method in this comparative example and the known anionicity is δ9=︱28.4%-31.2%︱ / 31.2%×100%=9%.

[0113] It can be seen from the test results of the embodiments and comparative examples that the anionicity obtained by the method for detecting the anionicity of polyacrylamide in the present invention is closer to the anionicity of the polyacrylamide sample, that is, the detection method of the present invention can obtain higher accuracy than the turbidimetry and precipitation methods.

[0114] At the same time, it can be seen from the test results of the embodiments and comparative examples that when the anionicity of polyacrylamide is low or high, the detection method of the present invention can obtain a more accurate anionicity.

[0115] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0116] For those skilled in the art, according to the concept of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A method for effectively detecting the anionicity of polyacrylamide, characterized in that: The steps include: S1: Transfer the polyacrylamide powder to the current collector and press it into a working electrode; S2: Assembling the working electrode, the counter electrode and the reference electrode into a three-electrode system; S3: placing the three-electrode system in an electrolyte solution, and detecting a current response curve of the three-electrode system at different potentials; S4: calculating the content of charged groups in the polyacrylamide dry powder according to the current response curve; S5: Calculating the anionicity of the polyacrylamide powder according to the content of the charged groups and the molar number of the polyacrylamide powder.

2. The method for effectively detecting the anionicity of polyacrylamide according to claim 1, characterized in that: The calculation formula of the anionicity is: the anionicity=the number of moles of the charged groups / the number of moles of the polyacrylamide×100%.

3. The method for effectively detecting the anionicity of polyacrylamide according to claim 1, characterized in that: The current response curve of the three-electrode system at different potentials is detected by cyclic voltammetry or constant potential method.

4. The method for effectively detecting the anionicity of polyacrylamide according to claim 1, characterized in that: Calculating the content of charged groups in the polyacrylamide dry powder according to the current response curve comprises the following steps: integrating the current response curve to calculate the quantity of electricity at different potentials; and calculating the content of charged groups in the polyacrylamide dry powder according to the quantity of electricity.

5. The method for effectively detecting the anionicity of polyacrylamide according to claim 1, characterized in that: In the process of detecting the current response curve of the three-electrode system at different potentials, the potential range is -0.5V-1V and the scanning speed is 5mV / s-50mV / s.

6. The method for effectively detecting the anionicity of polyacrylamide according to any one of claims 1 to 5, characterized in that: The particle size of the polyacrylamide dry powder is 20 μm-75 μm.

7. The method for effectively detecting the anionicity of polyacrylamide according to any one of claims 1 to 5, characterized in that: The concentration of the electrolyte in the electrolyte solution is 0.1 mol / L-0.5 mol / L; the electrolyte in the electrolyte solution includes one or more of sodium chloride, sodium sulfate and potassium chloride.

8. The method for effectively detecting the anionicity of polyacrylamide according to any one of claims 1 to 5, characterized in that: The thickness of the current collector is 0.1 mm-0.5 mm; the material of the current collector includes one or more of platinum, gold and silver.

9. The method for effectively detecting the anionicity of polyacrylamide according to any one of claims 1 to 5, characterized in that: The pressing pressure is 5MPa-10MPa; the pressing time is 8min-15min.

10. The method for effectively detecting the anionicity of polyacrylamide according to any one of claims 1 to 5, characterized in that: The material of the counter electrode includes platinum, and the reference electrode is a saturated calomel electrode.

Citation Information

Patent Citations

  • Method for determining ion content of cationic polyacrylamide by utilizing spectrophotometry

    CN101655461A

  • Method for testing hydrolysis degree and anion degree of partially hydrolyzed polyacrylamide containing AMPS

    CN115469054A